Gymnema sylvestre saponins for potential antifungal action: in vitro and in silico perspectives - Neel, Shila; Mandal, Abhishek; Saha, Supradip; Das, Amrita; Kundu, Aditi; Singh, Anupama (Frontiers in Plant Science, 2025)
Saponins are responsible for a wide range of biological activities, which is why the present research is focused on the chemical profiling of saponins and other metabolites from Gymnema sylvestre leaves for their potential efficacy in managing pathogenic fungi. Leaves of the plant was extracted with chloroform to obtain crude saponin concentrates. Characterizations of the chloroform soluble fraction of the leaves [chloroform extract of G. sylvestre (CGS)] in ultra-performance liquid chromatography–quadrupole time of flight–electrospray ionization–tandem mass spectrometry (UPLC-QToF-ESI-MS/MS) displayed 23 metabolites, primarily comprising of saponins and other minor phytocomponents. Among these, two major saponins, gymnemic acid IV and gymnestrogenin, were isolated, purified, and characterized using 1H-NMR, 13C-NMR, and high-resolution mass spectrometry (HRMS). In vitro fungistatic efficacy showed the highest effectiveness against Penicillium digitatum 6952 (EC50 297.2 μg/mL), followed by Penicillium expansum 2995 (360.5 μg/mL) and Aspergillus flavus 6678 (369.4 μg/mL). Furthermore, the mechanism of interaction of these metabolites to inhibit cyt P450 sterol 1,4-α-demethylase was determined by in vitro and in silico molecular modeling analysis, explaining the probable reason for the reduction in ergosterol content in the treated fungi. In silico analysis suggested the highest binding efficiency of gymnemic acid IV due to the lowest binding energy, specifically interacted through conventional H-bonds, hydrophobic π-alkyl, π-π, and π-sigma interactions. Indeed, the valuable findings of the study would be useful for further development of Gymnema saponin based biopesticidal products.